MOLECULAR CHARACTERIZATION AND MULTI-DRUG-RESISTANT PROFILES OF UROPATHOGENIC ESCHERICHIA COLI FROM ADULTS ATTENDING NATIONAL ORTHOPEDIC HOSPITAL ENUGU, NIGERIA (Journal of Biomedical Investigation, 2025)
Background: Antimicrobial resistance (AMR) in Escherichia coli poses a significant challenge in both community and hospital settings. Aim: The study aimed to ascertain the prevalence, molecular types and susceptibility pattern of multidrug resistance patterns of E.coli isolated from urine of adults with urinary tract infections attending National Orthopaedic Hospital, Enugu Nigeria.Materials and Methods: Two hundred and thirty (230) urine samples were collected from adults aged 18-65 years attending the hospital using sterile screw capped containers. Structured questionnaire was used to obtain the demographic data of the participants. Urine samples were inoculated directly onto MacConkey agar, CLED and Chrome agar using streak plate method and incubated at 370C for 24 hrs. Colonies were identified based on their cultural, morphological and biochemical characteristics. Antimicrobial susceptibility and resistance of the isolates were determined by Kirby Bauer standard disc diffusion method on Mueller Hinton agar. Molecular analysis was done using multiplex and Linear PCR on multidrug resistant E. coli isolates. Results: Out of the 230 samples analysed, 60(26.08%) were positive for E. coli, of which 42(24.9%) were obtained from the female participants, suggesting a gender-based predisposition to UTIs(p>0.05). Age group 35-45 years had the highest prevalence (31.14%) of infection. Out of the 60 samples positive for E.coli, 25( 41.66%) were multidrug resistant E. coli. The result shows that there was no statistically significant (p>0.05) association between gender, age in multidrug resistant E. coli. The E.coli isolates were highly resistant (86.6%) to Streptomycin and Penicillin, and had least resistance to Nitrofurantoin (1.66%). Molecular analysis identified the presence of blaCTX-M and blaTEM resistance genes, while blaSHV was not detected. All the isolates resistant to Streptomycin and Penicillin were positive for blaTEM genes, while the isolates resistant to Nalidixic acid, Amoxicillin-clavulanic acid and Trimethoprim-Sulfamethoxazole were positive for blaCTX-M genes. Conclusion: The high level of resistance to commonly used antibiotics and the detection of resistance genes such as blaCTX-M and blaTEM highlights the growing threats of antimicrobial resistance in the area.
Keywords: Multidrug resistant; molecular characterization; E.coli; UTIs